URGENSITAS MAHKAMAH KONSTITUSI MENGELUARKAN FATWA HUKUM DALAM PEMBENTUKAN UNDANG-UNDANG - Achmad Safiudin R; Jazim Hamidi; Tunggul Anshari (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
Writing this scientific article discusses the urgency of the Mahkamaha Constitution to issue a legal fatwa in the formulation of laws. Based on the idea that the making of laws which constitute the rules of implementing the constitution, constitutional questions are not impossible to emerge at the time of the formation of laws by state legislatures, because the norms of constitutional material are abstract in nature. Therefore an alternative effort is needed, namely the submission of questions to the Constitutional Court regarding the norms of the articles of the Constitution, which relate to the laws to be made / form. Through these questions, a fatwa or legal consideration was issued from the Constitutional Court, so that the DPR and the President did not appear different interpretations in fulfilling the original intent of the constitution and meeting the constitutional rights of citizens. The writing of scientific articles uses empirical juridical research methods. The results of this scientific article are the legal fatwa of the Constitutional Court as the theoretical implications of the authority to examine the constitutionality of laws against the 1945 Constitution of the Republic of Indonesia can be based on a commitment to prevent acts of state administration which are not in accordance with the constitution as the highest state law. In addition, constitutional testing of the draft law through interpretation of the constitution constitutes control between state institutions (cheks and balances) to realize the ideals of a democratic legal state that prioritizes constitutional supremacy.